Evolutionary Design of Active Free Space Optical Networks Based on Digital Mirror Devices - Limmer, Steffen; Fey, Dietmar; et al. (Applications of Evolutionary Computation, 2012)
Optical connections have several advantages compared to conventional electrical connections, especially a higher attainable bandwidth. While long distance optical connections are already established, optical board- and chip-level connections are still a subject of current research. In this paper we describe a new setup for optical board-level connections which is based on free space optics and allows the switching of signals within the optical domain. We describe the evolutionary optimization of design parameters for the proposed setup, done with a memetic evolutionary algorithm and present the optimization results. © 2012 Springer-Verlag.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD3.evolut
Keywords: CMA-ES; digital mirror device; Evolutionary algorithm; optical connection; PIFSO